Proceedings of the 6th International Conference on Multimodal Interfaces 2004
DOI: 10.1145/1027933.1027970
|View full text |Cite
|
Sign up to set email alerts
|

User walkthrough of multimodal access to multidimensional databases

Abstract: This paper describes a user walkthrough that was conducted with an experimental multimodal dialogue system to access a multidimensional music database using a simulated mobile device (including a technically challenging four-PHANToM-setup). The main objectives of the user walkthrough were to assess user preferences for certain modalities (speech, graphical and haptictactile) to access and present certain types of information, and for certain search strategies when searching and browsing a multidimensional data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…These are again monosemic objects as they associate one piece of information. Van Esch-Bussemakers and Cremers [79] utilized a complex setup of four PHANTOMs, with their motion restricted to a straight line, along with vibrotactile actuators integrated in the gimbals to simulate a mobile device. The setup was used to experiment how users could access a multidimensional music database.…”
Section: A Monosemic Objects -Haptic Icons and User Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…These are again monosemic objects as they associate one piece of information. Van Esch-Bussemakers and Cremers [79] utilized a complex setup of four PHANTOMs, with their motion restricted to a straight line, along with vibrotactile actuators integrated in the gimbals to simulate a mobile device. The setup was used to experiment how users could access a multidimensional music database.…”
Section: A Monosemic Objects -Haptic Icons and User Interfacesmentioning
confidence: 99%
“…While on the other hand, specific modalities may be better at displaying certain data; and be most relevant to a particular task. For instance, van Esch-Bussemakers and Cremers [79] investigated the use of different modalities to operate different functions; concluding "that participants did have preferences for certain modalities when handling certain types of information".…”
Section: Tablesmentioning
confidence: 99%
“…employed multi-modal stimuli carrying an affective load obtaining a multimodal affective congruency effect in several studies (e.g. see Van Esch-Bussemakers 2001, Lemmens et al 2001.…”
Section: Affective Compatibilitymentioning
confidence: 99%
“…Lemmens, Bussemakers and colleagues (e.g. see Van Esch-Bussemakers 2001, Lemmens et al 2000) have used the major/minor distinction repeatedly to construct earcons that carry an affective charge in various studies involving a simple picture-categorization task. They found that the positive affective valence of the major mode (expressed as, e.g.…”
Section: The Major/minor Distinctionmentioning
confidence: 99%